PERBEDAAN PENGARUH METODE LATIHAN FARTLEK DAN INTERVAL TERHADAP DAYA TAHAN (ENDURANCE) - Taufik Nanda Aditiya; Waluyo Waluyo; Ahmad Septiandika Adirahma (PHEDHERAL, 2018)
The purpose of this study is to determine: (1) To test whether there is influence of the application of fartlek and interval training methods to endurance in extracurricular students futsal SHS 3 Sukoharjo 2016/2017, (2) More effective and efficient between fartlek and interval training on Endurance in extracurricular students of SHS 3 Sukoharjo year 2016/2017. The type of research used is quantitative experimental research. Subjects used in this study are extracurricular students futsal SHS 3 Sukoharjo 2016/2017. The number of learners is 30 students. The entire subject is used as the research sample. The data collected in this research is Endurance data about VO2 Max capacity. The tests and measurements used to collect data are by performing the Multistage Fitness Test (MFT) test. The data analysis technique used in this research is the difference test (t-test) by passing the first requirement test such as normality test and homogeneity test. The result of the study was: (1) There was a significant comparison of the effects of fartlex training method and interval training on energency participants in futsal extracurricular leaners of SHS 3 SUKOHARJO year 2016/2017, (t count = 2,6651 > 1,7613); (2) Interval training methods better than fartlek training method for energency participants in futsal extracurricular leaners of SHS 3 SUKOHARJO year 2016/2017. Based on the precentage increase of physical endurance showed that group 2 (who received treatment with interval training method was 5,64% > group 1 (who received treatment fartlek training method) was 2,62%. The conclude of the result as: (1) There was a comparison of the effects of fartlex training method and interval training on energency participants in futsal extracurricular leaners of SHS 3 SUKOHARJO year 2016/2017; (2) Interval training method better than fartlek training method on the physical endurance of extracurricular learners SHS 3 SUKOHARJO year 2016/2017.